Regulatory issues [what is the QSR - Bartoo, G.
Mention good manufacturing practice (GMP) or quality system regulation (QSR) and many engineers will immediately think of mounds of questionably meaningless paperwork. Is that really what the QSR is about? Or is that impression brought about by bad implementations of the QSR and a lack of understanding as to why medical manufacturers need the QSR? This article gives more of an overview as to what the key ideas are behind the QSR.
Keywords: Control and feedback loop; Design control; Good manufacturing practice; Medical device manufacturers; Quality system regulation; Redesign cycles; Testing; Verification